2004
DOI: 10.1086/424518
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of a Rapid Molecular-Based Assay for the Diagnosis of Group B Streptococcus Colonization in Pregnant Women

Abstract: Use of this test for determination of GBS colonization during labor is highly sensitive and specific and may lead to a further reduction in rates of neonatal GBS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
3
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 33 publications
10
89
3
7
Order By: Relevance
“…In a clinical trial published in 2004, the IDI-Strep B TM assay demonstrated a sensitivity of 94 % and a specificity of 96 % compared with intrapartum cultures. It was revealed to be more sensitive than an antenatal reference culture or a risk-based strategy to predict GBS colonization status at delivery [30]. The superiority of the intrapartum molecular detection of GBS when compared with antenatal culture was confirmed by a Canadian group [31].…”
Section: Polymerase Chain Reactionmentioning
confidence: 92%
“…In a clinical trial published in 2004, the IDI-Strep B TM assay demonstrated a sensitivity of 94 % and a specificity of 96 % compared with intrapartum cultures. It was revealed to be more sensitive than an antenatal reference culture or a risk-based strategy to predict GBS colonization status at delivery [30]. The superiority of the intrapartum molecular detection of GBS when compared with antenatal culture was confirmed by a Canadian group [31].…”
Section: Polymerase Chain Reactionmentioning
confidence: 92%
“…Rapid real-time PCR assays for GBS detection have been further developed and their performances have been evaluated these last years as summed up in Table 2. When compared to enriched GBS cultures, sensitivity and specificity for PCR tests range from 62.5%-100% and 84.6-100% while PPV and NPV range from 65-100% and 92.3-100% [80,82,[84][85][86][103][104][105][106][107][108][109][110][111]. Today, real-time PCRbased tests (NAAT) can equal or surpass the sensitivity of antenatal culture at 35-37 weeks' gestation and compare favorably with reference to bacterial culture performed at presentation for delivery taken as gold standard for the detection of GBS colonization [80,82,101,102,112].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 98%
“…Studies have showed utility to assess intrapartum GBS colonization and thus avoiding need for antenatal screening, but they remain limited [80]. At least, rapid real-time PCR assays offer the advantage of GBS detection among women delivering preterm, women without antenatal care or in whom no antenatal culture was performed, or women for whom no result was available at delivery as mentioned in the revised 2010 CDC recommendations.…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…La colonización se produce por la exposición del recién nacido al microorganismo durante el parto a partir del tracto genital materno colonizado, o en el útero por vía ascendente, siendo la tasa de transmisión vertical del 50% [1][2][3][4] . La importancia de realizar tamización de colonización de las gestantes antes del parto, radica en definir el empleo de antibióticos profilácticos para prevenir el desarrollo de la infección.…”
Section: Introductionunclassified